Single-stranded DNA (ssDNA) donor repair templates and CRISPR/Cas9 enable a high-frequency of targeted insertions in potato - González, Matías N.; Salaria, Neha; Friberg, Martin; Liu, Ying; Alverup, Josefin; Andersson, Mariette; Hofvander, Per (Frontiers in Genome Editing, 2025)
Homology-directed repair (HDR) holds great promise for plant genetic engineering but remains challenging due to its inherently low efficiency in gene editing applications. While studies in animal systems suggest that the structure of the donor repair template (DRT) influences HDR efficiency, this parameter remains largely unexplored in plants. In this study, we combined protoplast transfection with next-generation sequencing to analyse the impact of DRT structure on HDR efficiency in potato. A highly efficient ribonucleoprotein (RNP) complex targeting the soluble starch synthase 1 (SS1) gene was used in combination with various DRTs, differing in structural factors such as homology arm (HA) length, strandedness (i.e., ssDNA vs. dsDNA), and sequence orientation in ssDNA donors. Our results indicate that a ssDNA donor in the target orientation outperformed other configurations, achieving a HDR efficiency of 1.12% of the sequencing reads in the pool of protoplasts. Interestingly, HDR efficiency appeared independent of HA length. Notably, a ssDNA donor with HAs as short as 30 nucleotides led to targeted insertions in up to 24.89% of reads on average, but predominantly via alternative imprecise repair pathways, such as microhomology-mediated end joining (MMEJ). This donor structure also consistently yielded the highest HDR and targeted insertion rates at two out of three additional loci tested, offering valuable insights for future genome editing strategies in potato. We further assessed strategies to favour HDR over alternative repair outcomes, including the use of small molecules known to inhibit competing pathways in animal systems, and modifications to DRTs to enhance their availability in the vicinity of the target site. However, these approaches did not improve HDR efficiency. Overall, this study presents an effective platform for rapidly assessing gene editing components in potato and provides insights for achieving high-frequency, targeted insertions of short DNA fragments, especially relevant for efficient knock-in integration in non-coding genomic regions.